Chebyshev chaotic polynomials for MIMO radar waveform generation. Issue 2 (1st February 2017) - Esmaeili Najafabadi, Hamid; Ataei, Mohammad; Sabahi, Mohamad Farzan
Abstract : In this study, the use of a family of Chebyshev chaotic maps for pulse compression in multiple input–multiple output (MIMO) radars is studied. It is shown that, these one‐dimensional chaotic maps, which are amongst the simplest chaotic systems, can produce arbitrary number of sequences with arbitrary length, low peak‐to‐average power ratio (PAPR), high merit factor (MF) or equivalently low integrated side‐lobe ratio (ISLR), very low peak side‐lobe ratio and low cross‐correlation levels. The complexity of algorithm for generating sequences in this method is linear. Besides, because of the flat spectrum of the generated sequences, high spectral efficiency can be achieved utilising these sequences. Moreover, simplicity of the map results in cheap building blocks of MIMO radars. Additionally, a simple method to improve the autocorrelation side‐lobe is given. By lowering the autocorrelation side‐lobes, ISLR or equivalently MF is enhanced. Nevertheless, in comparison with well‐designed unimodular sequences, the produced sequences show higher PAPRs. By utilising a PAPR reduction mechanism, this shortcoming is alleviated.